Transformation of Higher Education Quality Assurance: Challenges for Private Universities and Lecturers in the Implementation of RMHEST Number 39 of 2025 - Agus Salim Chamidi; Siti Fatimah (Yayasan Arfah Bin Haji Muhammad Saleh, 2026)
This study examines the implications of Regulation of the Minister of Higher Education, Science, and Technology (RMHEST) Number 39 of 2025 concerning Higher Education Quality Assurance for private higher education institutions and lecturers in Indonesia. This new regulation marks a paradigm shift from an orientation toward meeting National Higher Education Standards toward achieving international standards and about Recognition of Prior Learning (RPL). This study uses literature review and policy analysis to identify the structural, operational, and human resource challenges faced by private higher education institutions and lecturers. The results indicate that private higher education institutions face significant challenges in infrastructure, lecturer capacity, funding, and internal quality assurance systems. Meanwhile, lecturers are faced with demands to improve international competency, adaptation to curriculum flexibility, and master the RPL assessment system. This study concludes that the implementation of the RMHEST 39/2025 requires a comprehensive adaptation strategy, strong institutional support, and multi-stakeholder collaboration to ensure the successful transformation of higher education quality in Indonesia.